Towards Equitable Access: Improving Library Services for Distance Learning Students - Atuase, Diana; Maluleka, Jan; Ayensu, Eunice (Libri (København), 2024)
The plans and activities of academic libraries revolve around a user-centered approach to make noticeable improvements in the use of library resources and services. The purpose of this study was to examine library support strategies for the effective utilization of library support services and resources by distance-learning students. The research was conducted at the University of Education, Winneba, and the University of Cape Coast with distance learning students. A mixed-method approach was used, with 1170 students participating in quantitative research and 12 students and six (6) librarians participating in qualitative research, with Input-Environment-Output Model guiding the study. The findings of the study identified a lack of organized strategies for the use of library resources and services among distance learning students. The study proposed a model to improve the use of library resources and services among distance learning students.